Byzantine Epirus : a Topography of Transformation. Settlements of the Seventh-Twelfth Centuries in Southern Epirus and Aetoloacarnania, Greece. - Veikou, Myrto (Medieval Mediterranean., 2012)
Drawing on archaeological fieldwork in Western Greece, this book offers a fresh model for interpreting the transformation of medieval settlement (600-1200 AD). Rereading Byzantine texts from a postmodern theoretical background, it introduces a new perception of the historicity of space.